A Preliminary Study on the Feasibility of Gene Expression Profile of Rhesus Monkey Detected With Human Microarray - Lu, Y.; Wang, L.; Jin, X.; Chen, Younan; Cong, C.; Yuan, Y.; Li, Y.; Tang, W.; Li, H.; Wu, X.; Li, Y.; Wang, L.; et al. (2008)
Objectives: A pig-to-monkey transplant model was initiated to investigate the outcome of pig-to-human xenotransplantation. Though monkey is close to human in biology and physiology, the genetic differences between the two species remains unclear. This study sought to compare the gene expressions of three tissues from humans and rhesus monkey. Methods: RNA samples extracted from liver, spleen, and peripheral blood cells were hybridized onto Illumina gene expression microarray. Genes with detected signals greater than 1000 and diff-scores higher than 100 were selected as significant results. The data were analyzed with Illumina software. mRNA expression levels were confirmed by semiquantitative reverse transcriptase polymerase chain reaction (RT-PCR) analysis. Results: Of the 47,293 transcripts tested on every gene chip, more than 6000 genes were expressed in three tissues. Total numbers of genes detected and the similarity ratios followed the same rule as liver < PBC < spleen. The 136 IRI-related genes, 192 immunological-related genes, and 131 cell cycle-related genes selected and analyzed showed gene expression concordance rates of 82.35%, 72.92%, and 77.10%, respectively. RT-PCR tests indicated similar mRNA expression levels of RTN4, interleukin (IL)-1ß, NF-?B1, IL-8, and G0S2 to the results on chips. Conclusions: The detected mRNA expressions in human and monkey tissues showed an average consistency in 85.78%, indicating that a human microarray might provide a part of the information for monkey sample testing. Therefore, in pig-to-monkey transplant models, monkey microarray may be used to determine recipient gene expressions. The genetic difference between human and monkey must be taken into account in interpreting the experimental results. © 2008 Elsevier Inc. All rights reserved.